Evaluasi Kualitas Sistem Informasi Akademik STMIK PPKIA Tarakanita Rahmawati Dengan Metode WebQual - Muhammad Fadlan; Ummi Syafiqoh; Rosmini Rosmini; Asmah Asmah (Jurnal Komputer Terapan, 2020)
Academic information system is one of the important elements in the world of education, especially in tertiary institutions. Most of the users of information systems are students. Measurement of the quality of an information system is an important thing to do to maintain the sustainable use of the information system. At present, the STMIK PPKIA Tarakanita Rahmawati as one of the private tertiary institutions does not yet know for sure the quality of the academic information system from the user's side. Therefore, in this study measurement or evaluation of the academic information system website will be carried out using the WebQual method. The results of 113 respondents consisting of 62 female students and 51 male students can be concluded that of the three dimensions of Webqual, the Usability Quality dimension has the highest conformity rate of 82.82%. Meanwhile, the dimension that has the lowest conformity level is the Interaction Quality dimension with a value of 70.91%.